The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/elps.201300446
|View full text |Cite
|
Sign up to set email alerts
|

The development of a counterflow‐assisted preconcentration technique in capillary electrophoresis electrospray‐ionization mass spectrometry

Abstract: A preconcentration approach for CE-MS using counterflow-assisted electrokinetic injection was proposed. The proposed preconcentration method was based on a counterflow-compatible sheathless interface. The interface was fabricated using a capillary-assembled PDMS microdevice that allowed the application of a counterflow and provided liquid-film electrical conduction. During electrokinetic injection, a hydrodynamic counterflow was introduced into the separation capillary to retard the movement of the stacking bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…(Step 3 and 4) The inlet vial was replaced to low pH BGE and counterflow was stopped, where peptides are separated under the supporting flow by EOF. Reproduced from ref [58] with permission. case analyzing many analytes.…”
Section: Dynamic Ph Junctionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Step 3 and 4) The inlet vial was replaced to low pH BGE and counterflow was stopped, where peptides are separated under the supporting flow by EOF. Reproduced from ref [58] with permission. case analyzing many analytes.…”
Section: Dynamic Ph Junctionmentioning
confidence: 99%
“…Wang et al developed novel interface system for counterflow-assisted FASI as shown in Fig. 4 [58]. By fabricating a PDMS-made cross channel, they supply both sheath liquid and counter-flow to the separation capillary.…”
Section: Field-amplified Sample Stacking and Related Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first stacking implemented in CE‐ESI‐MS was transient ITP . Since 2013, stacking in CE‐ESI‐MS has been achieved by transient ITP as well as by field amplification/enhancement and dynamic pH junction . Field‐enhanced sample injection (FESI) involves electrokinetic injection of a sample prepared in low conductivity diluent .…”
Section: Analytical Figures Of Merit and Sef For Fesi‐mss‐cze‐msmentioning
confidence: 99%
“…The interface was applied to the analyses of a five‐peptide mixture in low‐EOF (60 nL/min) and high‐EOF (210 nL/min) conditions and showed the stability and versatility of the emitter (Wang & Her, ). The same group of Wang and Her adapted their interface so a counterflow can be applied to the outlet side of the capillary and thereby accommodating counterflow electrokinetic supercharging (see sample loading Section 6) (Wang & Her, ). This interface design has only been used and reported by this group and no applications in bottom‐up proteomics have been reported to date.…”
Section: Interfacingmentioning
confidence: 99%